Luteinizing hormone and GATA4 action in the adrenocortical tumorigenesis of gonadectomized female mice - Doroszko M.; Chrusciel M.; Stelmaszewska J.; Slezak T.; Rivero-Müller A.; Padzik A.; Anisimowicz S.; Wolczynski S.; Huhtaniemi I.; Toppari J.; Rahman N.A. (S. Karger AG, 2022)
Background/Aims: Physiological role of luteinizing hormone (LH) and its receptor (LHCGR) in adrenal remains unknown. In inhibin-α/Simian Virus 40 T antigen (SV40Tag) (inhα/Tag) mice, gonadectomy-induced (OVX) elevated LH triggers the growth of transcription factor GATA4 (GATA4)-positive adrenocortical tumors in a hyperplasia-adenoma-adenocarcinoma sequence.
Methods: We investigated the role of LHCGR in tumor induction, by crossbreeding inhα/Tag with Lhcgr knockout (LuRKO) mice. By knocking out Lhcgr and Gata4 in Cα1 adrenocortical cells (Lhcgr-ko, Gata4-ko) we tested their role in tumor progression.
Results: Adrenal tumors of OVX inhα/Tag mice develop from the hyperplastic cells localized in the topmost layer of zona fasciculata. OVX inhα/Tag/LuRKO only developed SV40Tag positive hyperplastic cells that were GATA4 negative, cleaved caspase-3 positive and did not progress into adenoma. In contrast to Lhcgr-ko, Gata4-ko Cα1 cells presented decreased proliferation, increased apoptosis, decreased expression of Inha, SV40Tag and Lhcgr tumor markers, as well as up-regulated adrenal- and down-regulated sex steroid gene expression. Both Gata4-ko and Lhcgr-ko Cα1 cells had decreased expression of steroidogenic genes resulting in decreased basal progesterone production.
Conclusion: Our data indicate that LH/LHCGR signaling is critical for the adrenal cell reprogramming by GATA4 induction prompting adenoma formation and gonadal-like phenotype of the adrenocortical tumors in inhα/Tag mice.